Blue carbon stock in mangroves and perception of blue carbon ecosystem by local communities in Eastern Visayas, Philippines - Asilo, Hannah Alexis M.
Additionally, the study establishes a connection between the perspective of local residents and the mechanisms associated with blue carbon. The utilization of vegetation indices in a multilinear regression model yielded an r2 value of 0.68. The findings indicate that the local communities possessed awareness regarding the benefits they could obtain from mangroves. However, the level of their awareness is contingent upon the type of benefit they actively obtain. The influence of personal experiences, such as natural disasters, on perceived threats has been observed, but recognized management strategies are shaped by local knowledge, including information and educational campaigns.